Results of a brief online group application of the unified protocol for the preventionof emotional disorders in university students: a pilot study with multiple baseline experimental design - Socías-Soler, Jordi; Martínez-García, Laura; Peris-Baquero, Óscar; Osma, Jorge (Anales de Psicología / Annals of Psychology, 2024)
Emotional disorders (EDs) are the most common disorders among the young population. The development of preventive programs for EDs is essential to avoid their possible appearance. Transdiagnostic prevention programs could present an advantage over existing ones to improve emotional regulation strategies. Thus, the objective of this study has been to determine the preliminary feasibility and effectiveness of a brief program based on the Unified Protocol (UP). The project consisted of a pilot study using a multiple baseline experimental design. Nine university students received a 5-session program based on the UP in online-group format. Significant differences were found after the intervention for emotion regulation, perceived social support and avoidance, with moderate-large effect sizes (Cohen's r = .49 - .59). These improvements showed increases at 1-month and 3-month follow-ups. Those results are in line with those showing that brief transdiagnostic preventive programs could be useful for the prevention of EDs in the university population.